Severe imbalance of cell proliferation and apoptosis in the left colon and in the rectosigmoid tract in subjects with a history of large adenomas. Issue 2 (1st February 2001) - Anti, M; Armuzzi, A; Morini, S; Iascone, E; Pignataro, G; Coco, C; Lorenzetti, R; Paolucci, M; Covino, M; Gasbarrini, A; Vecchio, FM; Gasbarrini, G
Abstract : BACKGROUND: Alterations in epithelial proliferation and apoptosis in colonic mucosa are associated with an increased risk of colon cancer. It is unclear if these alterations represent a generalised "field defect". AIMS: To analyse segmental patterns of cell proliferation and apoptosis in the colon of subjects with a high and no apparent risk of colon cancer. METHODS: Pancolonoscopy was performed in 15 patients with resected adenomas (⩾1.5 cm) and in nine subjects without an apparent risk of colorectal cancer. Mucosal biopsies were taken from the right colon, left colon, and sigmoid rectum. Crypt cell proliferation and apoptosis were evaluated, respectively, with bromodeoxyuridine immunohistochemistry and terminal deoxyuridine nucleotidyl nick end labelling of DNA strand breaks. Results are expressed as total labelling index (TLI) and labelling index (LI) for each of the five compartments in which colonic crypts were divided (fourth and fifth compartments were evaluated together) for cell proliferation and as apoptotic index (AI) for apoptosis assessment. RESULTS: No significant segmental variations in proliferation were found in either group. Compared with controls, adenoma patients had higher TLIs for the right (p>0.05), left (p<0.005), and sigmoid rectum (p<0.05) segments, and higher left colon LIs for crypt compartments (compartment 1, p<0.01; compartment 2, p<0.005; compartment 3, p<0.001; compartments 4–5, p<0.01). Control AIs were similar in all segments but in the adenoma patients left colon and sigmoid rectum AIs were lower than their right colon indexes (p<0.05, p<0.05) and corresponding values for controls (p<0.01, p<0.05). CONCLUSIONS: The colonic mucosa of patients with past adenomas presents diffuse hyperproliferation and, distally, abnormally distributed proliferating cells and markedly reduced apoptosis. These changes represent a significant risk for malignancies and could account for the high prevalence of left colon tumours.